Functional characterization of APC5 in Arabidopsis thaliana - Silva, Luís Felipe Correa da (2023)
As a multicellular organism, plants have their growth and development directly dependent on the cell division. This process brings together dozens of molecular reactions, which ensures cell proliferation in the most varied plant tissues. The four sequential phases that make up the cell cycle (S, G1, M and G2) have the presence and absence of different molecular components of the cell division program, such as cyclins, CDKs and securins, acting together in order to guarantee the unidirectional progression of the process, in an irreversible way. The ubiquitin-proteasome system (UPS) is a multi-enzymatic cascade that target specific substrates for degradation through 26S proteasome. The Anaphase Promoting Complex/Cyclosome (APC/C) is one of the enzymatic machines responsible for recognizing the substrate to be ubiquitinated by the UPS. In Arabidopsis thaliana, the APC/C has 14 subunits. Several studies have reported that perturbations in the expression levels of some subunits can lead to changes in the plant phenotype, and compromise process such as gametogenesis. The cell division process occurs in synchrony with the other metabolic processes of the cell, as well as of the entire plant. Changes in nutrients or even in intracellular demands can lead to changes in metabolites concentration and their conversion rates, altering the biological processes of the organism. Metabolic changes occur at a rate fast enough to escape transcriptional regulation, forcing the cell to use other ways to regulate its reactions to deal with these changes, such as the action of metabolites as regulators. In this way, this project aims to functionally characterize the APC5 gene from Arabidopsis thaliana, as well as to investigate the changes in the plant metabolism due to alterations in the expression levels of the APC5, possibly correlating the changes with already known process that drive plant growth. The results show that, although metabolic differences could not be detected, overexpression of the APC5 gene was able to change the total area of Arabidopsis rosettes, making them smaller in transgenic strains when compared to wild type. Furthermore, it can be detected that the promoter of the gene is active in the apical merisms of the plant, as well as in the meristem of the lateral roots. Assays with the APC5 protein fused to GFP show that it is located in the nucleus and cytoplasm.